An investigation of magnet effect via overnight returns: the Malaysian case - Mohamad, Azhar; Sifat, Imtiaz Mohammad; Hamid, Zarinah (Emerald, 2018)
Purpose – Magnet effect entails a hypothesis in market microstructure entailing a systemic likelihood of prices being sucked toward the theoretical threshold. The purpose of this paper is to investigate the existence of magnet effect in Bursa Malaysia via overnight returns. Design/methodology/approach – This study investigates the existence of magnet effect via overnight returns in Bursa Malaysia by utilizing historical daily price data from 1994 to 2017 by probabilistic regression approaches. The authors divide the study period into three distinct regimes based on regulatory limit mechanisms. Findings – Based on demarcated regimes, the authors find evidence of magnet effect in Bursa Malaysia throughout all regimes, with a heightened magnitude detected between 2002 and 2013. Moreover, upper limit scenarios exhibit a greater propensity for magnet effect. The authors end the paper with implications of the findings for portfolio managers, intraday traders, and policymakers. Originality/value – The research is the first of its kind in attempting to measure the magnet effect in Malaysia via overnight jumps